2000
DOI: 10.1159/000046508
|View full text |Cite
|
Sign up to set email alerts
|

Brain Natriuretic Peptide Is a Predictor of Anthracycline-Induced Cardiotoxicity

Abstract: Anthracyclines are effective antineoplastic drugs, but they frequently cause dose-related cardiotoxicity. The cardiotoxicity of conventional anthracycline therapy highlights a need to search for methods that are highly sensitive and capable of predicting cardiac dysfunction. We measured the plasma level of brain natriuretic peptide (BNP) to determine whether BNP might serve as a simple diagnostic indicator of anthracycline-induced cardiotoxicity in patients with acute leukemia treated with a daunorubicin (DNR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 18 publications
3
51
0
1
Order By: Relevance
“…Some studies concluded that there is an association between LV dysfunction and increased natriuretic peptide concentrations (16 -21 ). Only a few anecdotal reports (22)(23)(24)(25) exist on the potential role of ANP and/or BNP as markers useful for detecting subclinical cardiac dysfunction, whereas no reports have been published on the role of NT-proBNP.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies concluded that there is an association between LV dysfunction and increased natriuretic peptide concentrations (16 -21 ). Only a few anecdotal reports (22)(23)(24)(25) exist on the potential role of ANP and/or BNP as markers useful for detecting subclinical cardiac dysfunction, whereas no reports have been published on the role of NT-proBNP.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors studied the association and relationship between natriuretic peptides and diastolic LV dysfunction, and others simply checked systolic LV function. However, only a few studies 55,[63][64][65][66][67] evaluated the potential predictive value of natriuretic peptide concentrations to detect the ongoing development of cardiac dysfunction.…”
Section: Natriuretic Peptides As Markers Of Ct-induced Cardiotoxicitymentioning
confidence: 99%
“…Furthermore, this assay can add prognostic information for newly diagnosed patients more effectively than echocardiography and can be useful in designing therapeutic strategies and monitoring response (74 ). Another example is the possibility, mainly by BNP assay, of identifying HF related to anthracycline cardiotoxicity (66,(75)(76)(77)(78).…”
Section: Diagnostic Accuracy Of Cnh Assays In Patients With Acute Myomentioning
confidence: 99%